Western Balkans Regular Economic Report No. 13, Spring 2018 : Vulnerabilities Slow Growth - World Bank Group (World Bank, Washington, DC, 2018)
GDP growth in the Western Balkans slowed from 3.1 percent in 2016 to an estimated 2.4 percent in 2017. Regional growth in 2017 is less optimistic than the 2.6 percent expected when the Fall issue of this report was published. It slowed in Serbia due to a harsh winter and stalled in FYR Macedonia, where the political crisis deterred both public and private investment. Bosnia and Herzegovina (BiH) grew at a rate like the last two years. The dynamism of the smaller economies of Albania, Kosovo, and Montenegro drove regional growth in 2017, with support from higher growth in trading partners, a pickup in commodity prices, and the execution of large investment projects. Bold structural reforms are necessary if the region is to grow sustainably over the medium term. Regional GDP growth is projected to rise from 2.4 percent in 2017 to 3.2 percent in 2018 and 3.5 percent in 2019. Countries are expected to grow faster, pushed up by projected stronger growth in Europe, except for Albania, where moderation is expected as large investment projects are completed, and Montenegro, which is expected to undergo a much-needed fiscal consolidation. Among risks to the outlook are trade protectionism, normalization of interest rates globally, and low potential growth and uncertainty about domestic policy or policy reversals. These risks can be mitigated by rationalizing spending to build fiscal space for growth-enhancing reforms, and by a more strategic approach to boost competitiveness. Policies to lift physical and human capital, expand labor force participation, and improve market institutions should help raise growth potential and reduce inequality.